Мониторинг динамики работы пластинчатых подогревателей сахарного сока в рабочих условиях - Демирский, А. В.; Георгиадис, M. C.; Товажнянский, Леонид Леонидович; Арсеньева, Ольга Петровна; Капустенко, Пётр Алексеевич; Бабак, Татьяна Геннадиевна; Хавин, Геннадий Львович (НТУ "ХПИ", 2015)
Розглянуто роботу пластинчатих підігрівачів цукрового соку у реальних умовах експлуатації на цукровому заводі. Була визначена степінь забруднення усіх апаратів і встановлені строки виходу на чищення за критерієм збільшення втрат тиску у підігрівачі. Вивчена структура і склад відкладень, та їх розподіл у теплообміннику. Представлені виводи і рекомендації для раціонального проектування теплообмінних апаратів.

The work of the plate heaters sugar juice in actual use in a sugar factory is considered. It was determined the degree of fouling of all installed devices and time-to-clean under the criterion of increasing pressure drop in the unit. The structure and composition of the deposits and their distribution in the heat exchanger are studied. The conclusions and recommendations for the rational design of heat exchangers are presented.
Monitoring the dynamics of the work plate heat exchangers of sugar juice in operating conditions
Keywords: выпарка; сахарный завод; критическое значение; эксплуатация; продуты переработки